Maintenance of Dental and Oral Health of High Class Students Using Virtual Reality Box Media (Study at SDN Rejosopinggir Tembelang Jombang) - Rosa Amalia; Ida Chairanna Mahirawatie; Agus Marjianto (International Journal of Advanced Health Science and Technology, 2024)
Dental caries is one of the problems related to oral health that can affect overall health. The state of oral and dental health can be ascertained using the initial dental and oral examination data from the Jatiwates Tembelang Jombang Health Center. Specifically, the number of dental caries among high school students at SDN Rejosopinggir Tembelang Jombang, which shows an average DMF-T index of 5.9, can be used to inform this determination. A high DMF-T index falls between 4.5 and 6.5, according to the WHO. The problem in this study is the high school students in SDN Rejosopinggir Tembelang, Jombang Regency, had a high rate of dental cavities in 2023. The purpose of this study is to find out the difference in oral and dental health maintenance between high school students at SDN Rejosopinggir before and after using Virtual Reality Box material. The type of research is called a quasi-experiment, and it aims to enroll 43 students. The data collection method used is a questionnaire. Data findings are summarized and presented in tabular form as part of the data analysis technique. The results of the study is analysis of the Wilcoxon test showed that the ρ value was 0.000<0.05 with a pretest value of Mean±SD 57.67±12.216, and a posttest value of Mean±SD 77.91±11.032, then H1 was accepted and H0 was rejected, meaning that Students' understanding of maintaining their oral and dental health can be improved by the Virtual Reality Box media.